Submaximal loading as a feasible alternative to supramaximal loading in accentuated eccentric loading during the short-term basic strength block - Caizheng Yue; Chunxiao Jia; Wenzheng Zha; Chenyu Zhang; Haokai Xu; Zhao Li (PLoS ONE, 2025)
Purpose The purpose of this study was to compare the effects of supramaximal and submaximal accentuated eccentric loading (AEL) on lower-body function and hypertrophy during a short-term basic strength block. Methods Twenty-two trained male students (20.64 ± 1.92 years, 177.07 ± 4.17 cm, 73.08 ± 4.44 kg) were assigned to two experimental groups based on baseline strength: the supramaximal loading group (SUPRA, 120%/70% one repetition maximum [1RM], n = 11) and the submaximal loading group (SUB, 95%/70% 1RM, n = 11), both groups applying eccentric overload during each repetition. Both groups trained twice weekly for 4 weeks (3 sets × 5 reps). The pre- and post-tests included rectus femoris cross-sectional area (RFCSA), countermovement jump height (CMJH), back squat 1RM, and 50% 1RM squat failure volume load (SFVL). Results A statistically significant main effect of time was observed for all variables (P < 0.05), but no statistically significant group × time interaction effects were found for any variable (P > 0.05). Both the SUPRA and SUB showed no statistically significant improvements in RFCSA, with trivial changes observed (P > 0.05, Hedges’ g = 0.13 and 0.10, respectively). Both the SUPRA and SUB showed statistically significant improvements in CMJH, 1RM, and SFVL (P < 0.05), with similar changes in CMJH (Hedges’ g = 0.31 and 0.22, respectively) and 1RM (Hedges’ g = 0.46 and 0.38, respectively). In SFVL, the SUPRA showed slightly greater improvements than the SUB (Hedges’ g = 0.43 and 0.19, respectively). Conclusions The results indicate that AEL training is effective in short-term training, with supramaximal and submaximal AEL producing similar improvements in outcomes. Therefore, submaximal AEL can serve as a feasible alternative to supramaximal AEL for physically active and healthy practitioners in a short-term basic strength block.